Big data: oportunidades e desafios da gestão pública local na criação de cidades mais inteligentes - Moura Filho, Joaquim Nerson (2024)
The rise of the digital era and the proliferation of connected devices have triggered an avalanche of data, known as big data, which has proven to be a promising source of evidence for public management. The research is motivated by the growing challenge of demystifying the use of big data by local governments, where there is low adoption, aiming to enhance the efficiency of public policies, the quality of life for residents, and the sustainability of cities. Exploring the opportunities and challenges inherent in its use. In this context, it is considered imperative to examine the different aspects involved, from data collection and processing to the formulation of evidence-based public policies. Technological challenges, qualified technical staff, political support from local leaders, legal frameworks, ethical issues of privacy and data security must be carefully considered when implementing big data-based solutions. A guide will be presented to illustrate how a city can implement a big data solution.